Thermal decomposition of solid state compounds of lanthanide and yttrium benzoates in CO2 atmosphere - Locatelli, José Roberto; de Siqueira, Adriano Buzutti; de Carvalho, Cláudio Teodoro; Ionashiro, Massao (Eclética Química, 2008)
Solid-state Ln-Bz compounds, where Ln stands for trivalent lanthanides and Bz is benzoate have been synthesized. Simultaneous thermogravimetric and differential thermal analysis in a CO2 atmosphere were used to study the thermal decomposition of these compounds